[1911 Women's Basketball team] - Frank Aston::::::photographer::: (1911)
Group portrait of 1911 women's basketball team in athletic garb; 7 members standing; basketball painted 'CPS '11.' Published in Polytechnic J. (v.6, no.8, June 1911)